Common Carpet Beetle Anthrenus scrophulariae (Linnaeus) (Insecta: Coleoptera: Dermestidae) - Stephanie K. Larrick; Mark Mitola (EDIS)
EENY482, a 4-page illustrated fact sheet by Stephanie Larrick and Mark Mitola, is part of the Featured Creatures collection. It describes this small blackish beetle that is found worldwide and infests goods made from animal products, such as carpets, wool, textiles, and preserved museum specimens — distribution, description, life cycle, economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, September 2010.